EACVI survey on investigations and imaging modalities in chronic coronary syndromes. (9th November 2020) - Bularga, Anda; Saraste, Antti; Fontes-Carvalho, Ricardo; Holte, Espen; Cameli, Matteo; Michalski, Blazej; Williams, Michelle C; Podlesnikar, Tomaz; D'Andrea, Antonello; Stankovic, Ivan; Mills, Nicholas L; Manka, Robert; et al.
Abstract: Aims: The European Association of Cardiovascular Imaging (EACVI) Scientific Initiatives Committee performed a global survey to evaluate current practice for the assessment and management of patients with suspected and confirmed chronic coronary syndromes. Methods and results: One-hundred and ten imaging centres from 37 countries across the world responded to the survey. Most non-invasive investigations for coronary artery disease were widely available, except cardiovascular magnetic resonance (available 40% centres). Coronary computed tomography angiography (CCTA) and nuclear scans were reported by a multi-disciplinary team in only a quarter of centres. In the initial assessment of patients presenting with chest pain, only 32% of respondents indicated that they rely on pre-test probability for selecting the optimal imaging test while 31% proceed directly to CCTA. In patients with established coronary artery disease and recurrent chest pain, respondents opted for stress echocardiography (27%) and nuclear stress perfusion scans (26%). In asymptomatic patients with coronary artery disease and an obstructive (>70%) right coronary artery stenosis, 58% of respondents were happy to pursue medical therapy without further testing or intervention. This proportion fell to 29% with left anterior descending artery stenosis and 1% with left main stem obstruction. In asymptomatic patients with evidence of moderate-to-severe myocardial ischaemia (15%), only 18% of respondents would continue medical therapy without further investigation. Conclusion: Despite guidelines recommendations pre-test probability is used to assess patients with suspected coronary artery in a minority of centres, one-third of centres moving directly to CCTA. Clinicians remain reticent to pursue a strategy of optimal medical therapy without further investigation or intervention in patients with controlled symptoms but obstructive coronary artery stenoses or myocardial ischaemia.